SOME ISSUES OF DEVELOPING STUDENTS’ CREATIVE ACTIVITY THROUGH THE TOOLS OF BUKHARA FOLK APPLIED DECORATIVE ART IN EXTRACURRICULAR ACTIVITIES - Shakhnoza Mansur kizi Mahmudova, (Journal of Applied Science and Social Science, 2025)
This article explores the theoretical and practical aspects of enhancing students’ creative activity during extracurricular sessions through the use of Bukhara folk applied decorative art elements. The study analyzes the potential of national patterns, colors, and compositional structures in developing aesthetic perception and fostering creative thinking. It also substantiates effective pedagogical methods that engage learners in artistic activities and strengthen their creative motivation. The findings present practical recommendations for improving extracurricular educational practices based on Bukhara folk decorative art.